Faktor-faktor Yang Mempengaruhi Penawaran Kopra - Ardiansyah Ardiansyah; Abdulrahim Maruwae; Meyko Panigoro; Radia Hafid (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2021)
This study aims to determine the magnitude of the effect of Price (X1) and Distribution Costs (X2), both simultaneously and partially on the Copra Supply (Y) in Bontomatene District, Selayar Islands Regency. The variables in this study consisted of the independent variable (independent variable), namely Price. and distribution costs while the dependent variable (dependent variable) in this study is the Copra Offer (Y). The population in this study were 28 copra traders living in Bontomatene District, Selayar Islands Regency. Data collection in this study used observation, interview and documentation techniques, while the analysis used was multiple linear regression analysis. The results showed that the supply factor was in the form of Price and distribution costs simultaneously have a positive and significant effect on copra supply in Bontomatene District, Selayar Islands Regency. And a partial analysis found that the relationship between price (X1) and distribution costs (X2) has a positive and significant effect on copra supply (Y).